Effect of organic substrates on germination and germ tube growth of vesicular-arbuscular mycorrhizal fungus spores in vitro - Siqueira, José Oswaldo; Hubbell, David H. (Pesquisa Agropecuaria Brasileira, 2014)
Vesicular-arbuscular mycorrhizal (VAM) fungi are obligate biotrophs and have not been grown in the absence of living roots. Pure culture of these fungi constitutes a critical prerequisite for intensive studies on their practical application. The effect of additional nutritional factors on spore germination and germ tube growth of surface disinfested spores of VAM fungi in vitro is reported. A range of organic substrates was tested. Most of them were inhibitory or had no effect on spores. However, small concentrations of D-galacturonic acid (1 g 1-1) enhaced spore germination and 4 g 1-1 sucrose and 1% soil extract agar improved germ tube growth. The beneficial effect of soil extract is concentrated in the protein fraction, which appears to account for the limited saprophytic ability of these fungi in soil.